Correlation between Handgrip Strength, Mobilization Function, Physical Activity Level, and Muscle Mass in Community-Dwelling Elderly in Bandung, West Java Province, Indonesia - Sari Sekarsari; Vitriana Vitriana; Irma Ruslina Defi (International Journal of Integrated Health Sciences, 2018)
Objective: To investigate correlation between handgrip strength, mobilization function, and physical activity level (PAL), and muscle mass in community-dwelling Indonesian elderly.Methods: This was a cross-sectional study 193 subjects aged 60–90 years. Handgrip strength was measured using handgrip dynamometer while the mobilization function was assessed by performing gait speed test. Global Physical Activity Questionnaire (GPAQ) was used to assess the participant’s PAL and Bio Impedance Analyzer was used to measure the participant’s muscle mass based on skeletal mass index.Results: Significant positive correlations were discovered between handgrip strength and walking speed (rs. 0.501; p<0.001), PAL (rs. 0.153; p=0.003), and muscle mass (rs. 0,452; p<0.001).Conclusion: Stronger handgrip determines greater mobilization function, physical activity level, and bigger muscle mass in community-dwelling Indonesian elderly. Keywords: Gait speed, handgrip strength, muscle mass, physical activity DOI: 10.15850/ijihs.v6n1.1047